Entre gestos: interações entre música e dança com mediação digital - Leandro Pereira de Souza (2018)
Recent technologies are responsible for an increasing number of cultural and research activities dealing with the association between music and movement, a relationship deeply rooted in every human culture. Gestures may explore diﬀerent types of energy and become the basis of expression and artistic creation. Starting from the investigation of the diﬀerent meanings of the concept of gesture, we propose strategies and tools for the development of musical creations that explore dance and music within the context of electroacoustic composition and interactive digital performances. In motion capture, we used position sensors and inertial measurement units. From these data, we developed a tool in Max/Msp focused on the classiﬁcation of gestures of dancers based on the Laban Movement Analysis. The sonic/musical approach is based on Schaeﬀer’s morphology and Smalley’s spectromorphology, which can rely on live instruments and recordings, and their processing in real time. Various possibilities of interaction between the gestures of the two modalities, thought at both local and structural levels, are proposed. Interactive pieces were elaborated, exploring diﬀerent possibilities opened by the two modalities.